2015
DOI: 10.1097/htr.0000000000000067
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammation After Severe Traumatic Brain Injury

Abstract: Chronic inflammation has not been well characterized following TBI. Our subacute cytokine load score classifies individuals at risk for unfavorable outcomes following injury. Higher proinflammatory burden with IL-6, relative to the anti-inflammatory marker IL-10, is significantly associated with outcome. Further research should examine whether inflammatory genes and other inflammatory biomarkers affect risk for unfavorable outcomes and TBI complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(87 citation statements)
references
References 23 publications
2
82
1
2
Order By: Relevance
“…This observation of increased IL-6 after moderate blast exposure in humans is unique, and consistent with the pre-clinical evidence which suggest central and peripheral IL-6 activity occurs after primary blast exposure (Kamnaksh et al, 2011). Increased IL-6 after blast exposure may have clinical ramifications, since pre-clinical blast studies and clinical studies of blunt-force TBIs report associations between central and peripheral IL-6 levels and poor outcomes (Kumar et al, 2015a; Kumar et al, 2015b; Minambres et al, 2003; Yang et al, 2013). Established physiological consequences of elevated IL-6 include ultrastructural changes in endothelial cells (Vajtr et al, 2009) and neuroinflammation (Erta et al, 2012; Kumar et al, 2015b; Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This observation of increased IL-6 after moderate blast exposure in humans is unique, and consistent with the pre-clinical evidence which suggest central and peripheral IL-6 activity occurs after primary blast exposure (Kamnaksh et al, 2011). Increased IL-6 after blast exposure may have clinical ramifications, since pre-clinical blast studies and clinical studies of blunt-force TBIs report associations between central and peripheral IL-6 levels and poor outcomes (Kumar et al, 2015a; Kumar et al, 2015b; Minambres et al, 2003; Yang et al, 2013). Established physiological consequences of elevated IL-6 include ultrastructural changes in endothelial cells (Vajtr et al, 2009) and neuroinflammation (Erta et al, 2012; Kumar et al, 2015b; Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, the identification of the acute phase protein C3 seems to be a promising candidate marker that is easily measured in human TBI biofluids. Recently, there has been increased interest in the inflammatory markers in neurotrauma that can be coupled with neural specific protein to constitute a panel of TBI markers; several of these inflammatory markers have shown to be elevated clinically after severe TBI (100). Similarly, identified structural proteins constitute an interesting set of markers to be assessed post-injury time points, since these protein families have been among grass root of acute TBI biomarkers (βII–αII spectrins, ankyrins) (101104).…”
Section: Resultsmentioning
confidence: 99%
“…Few studies investigated the cytokines blood levels during periods longer than 7 days (38, 39), and one report (40) investigated cytokines serum levels 3–6 months after the TBI.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have investigated inflammatory factors during slightly longer periods such as 7 days (36, 37), 14 days (38), or 22 days (39). Only one study (40) has reported elevated serum levels of IL-1β, IL-6, IL-8, IL-10, and TNF-α in TBI patients’ blood samples taken during the subacute and the chronic phase (3–6 months) after the injury.…”
Section: Introductionmentioning
confidence: 99%